Minimalisasi Biaya Obat Antihipertensi Lisinopril Atau Candesartan Pada Pasien Hipertensi Disertai Gagal Ginjal Kronik Di Instalasi Rawat Inap RSUD Dr. H. Abdul Moeloek - Anastya Devi Septiani; Putri Amelia Rooswita; Kiki Yuli Handayani (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2024)
Hypertension can damage blood vessels, which if not handled properly can cause kidney damage. Chronic Kidney Disease (CKD) is the most common comorbid in hypertensive patients in Indonesia with a percentage of 51%. The successful treatment of hypertension accompanied by CKD can be supported by administration of antihypertensives. The variety of antihypertensive therapy alternatives makes pharmacoeconomic studies necessary in order to obtain cost-effective therapy. The purpose of this study was to find out which antihypertensive drug is the most cost-minimizing between lisinopril and candesartan used in the treatment of hypertension accompanied by CKD (ICD-10 I12.0) in the Inpatient Installation based on the perspective of RSUD Dr. H. Abdul Moeloek in 2022. This research is a non-experimental observational with a purposive sampling technique. Data collection was carried out retrospectively from tracking secondary data originating from medical records, drug details in the Hospital Information System (SIRS), and details of direct medical costs in the Hospital Finance Department. Costs collected are in the form of direct medical costs which include antihypertensive drug costs, supporting drug costs, accompanying drug costs, laboratory costs, ICU, emergency room, hemodialysis, and hospitalization. The study showed that the average total cost of treating antihypertensive therapy for lisinopril was higher than candes artan, with lisinopril amounting to Rp 3.778.163 while candesartan was Rp 3.307.740. These results indicate that use of the antihypertensive candesartan is more cost-minimizing compared to lisinopril with a saving value of IDR Rp 470.423. Keywords: Pharmacoeconomics; CMA; hypertension with CKD; lisinopril; candesartan